ENHANCING LANGUAGE LEARNING THROUGH MEDIA TECHNOLOGIES: A FOCUS ON ENGLISH EDUCATION FOR YOUNG LEARNERS - Ikram Batirbaevich , Zarlikov (Өзбекстан Республикасы Илимлер Академиясы Қарақалпақстан бөлиминиң ХАБАРШЫСЫ, 2024)
The integration of media technology in English language education has become essential in improving gram- matical competence, particularly for A1 level students. This article explores the use of modern pedagogical meth- ods, media tools, and computer-based programs in teaching English in primary school classrooms. It highlights the role of media technology in enhancing students' imagination, increasing retention and developing individual abilities. By utilizing multimedia materials such as videos, audio and graphics, teachers can create engaging and effective lessons. The implementation of media technologies aligns with global trends in education, contributing to a more interactive and personalized learning experience for young learners.